Memory as a factor on shaping the desire of tourists - Đorđević Saša (University Educons, Faculty of Sports and Tourism, Novi Sad, 2016)
In the tourist practice and theory, great attention is paid to tourist events and experiences, as to the central element of tourist experience. In addition, what is important for tourists in the tourist cycle is not only to the number of events and tourist attractions, but also the intensity of their perception. Personal experiences are etched deeply in their consciousness and feelings and thus become unforgettable. Memory appears as a complementary categories to experiences, as the other side of the tourist experience and as an important element, making less or more influence on shaping and on character of the interests, needs and desires of tourists, as evidenced by the results of empirical studies that were analyzed in this paper.